Analysis of road traffic crashes in the State of Qatar. Issue 3 (3rd July 2019) - Timmermans, Chantal; Alhajyaseen, Wael; Al Mamun, Abdullah; Wakjira, Tadesse; Qasem, Moath; Almallah, Mustafa; Younis, Hassan
Abstract: Road traffic crashes (RTCs) are globally acknowledged as increasing threat to society, because they can affect many lives when they result in severe injury or fatality. In the State of Qatar RTCs are getting more awareness and attention, aiming to improve the traffic safety in the country. This study is an exploratory research providing different analyses of the crash data for seven consecutive years, ranging from 2010 to 2016, which is obtained from the Traffic Department in the Ministry of Interior for the State of Qatar. The objectives aim to evaluate the trend of RTC rate over time and create understanding of the influencing factors related to RTC frequency. Time series analyses show an increasing trend of RTCs leading to severe injury and a slight decreasing trend for fatal RTCs. Secondly, different RTC severity levels are related to diverse RTC causes. Furthermore, the results revealed that crashes with severe injuries or fatality for drivers as well as pedestrians are found to be significantly affected by seasonal weather variations, with the highest vulnerability in winter and autumn season. This study therefore suggests the implementation of strategies to prioritize the traffic safety of road users during the crash-prone winter and autumn seasons.